Ophiopogonin D′, a Natural Product From Radix Ophiopogonis, Induces in Vitro and in Vivo RIPK1-Dependent and Caspase-Independent Apoptotic Death in Androgen-Independent Human Prostate Cancer Cells - Lu, Zongliang; Wang, He; Zhu, Mingxing; Song, Wei; Wang, Jiajia; Wu, Changpeng; Kong, Ya; Guo, Jing; Li, Na; Liu, Jie; Li, Yanwu; Xu, Hongxia (Frontiers in Pharmacology, 2018)
Objective: The purpose of this study was to evaluate the anticancer effectsofOphiopogonin D` (OPD`, a natural product extracted from a traditional Chinese medicine (Radix Ophiopogonis) against androgen-independent prostate cancer cells and to explore the underlying molecular mechanism(s) of action. Methods: The CCK-8 assay was used to assess the viability of prostate cancer cells. The cell morphology was examined by an ultrastructural analysis via transmission electron microscopy. Cells in apoptosis (early and late stages) were detected using an Annexin V-FITC/propidium iodide kit with a FACSCaliber flow cytometer. JC-1, a cationic lipophilic probe, was employed to measure the mitochondrial membrane potential (MMP) of PC3 cells. Changes in the protein expression of RIPK1, C-RIPK1, caspase 8, cleaved-caspase 8, Bim, Bid, caspase 10 and cleaved-caspase 10 were evaluated by Western blotting. The mRNA expression of Bim was examined by quantitative real-time reverse transcription polymerase chain reaction. Z-VAD-FMK (a caspase inhibitor) and necrostatin-1 (a specific inhibitor of RIPK1) were utilized to determine whether the cell death was mediated by RIPK1 or caspases. PC3 and DU145 xenograft models in BALB/c nude mice were used to evaluate the anticancer activity of OPD`in vivo. Results: OPD`was shown to exert potent anti-tumor activity against PC3 cells. It induced apoptosis via a RIPK1-related pathway, increased the protein expression levels of RIPK1 and Bim, and decreased the levels of cleaved-RIPK1, caspase 8, cleaved-caspase 8, Bid, caspase 10, and cleaved-caspase 10. OPD` also increased the mRNA expression of Bim. The protein expression of Bim was decreased when cells were pre-treated with necrostatin-1. Treatment with OPD` inhibited the growth of PC3 and DU145 xenograft tumors in BALB/c nude mice. Conclusion: OPD` significantly inhibited the in vitro and in vivo growth of prostate cells via RIPK1, suggesting that OPD`may be developed as a potential anti-prostate cancer agent. Key words: Ophiopogonin D`; RIPK1; Bim; Apoptosis; Prostate cancer